Perception, Connotation, Translation of Numbers - Piccinini, Livio Clemente; Taverna, Mario; Chang, Margherita Ting Fa; Tubaro, Giovanni (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of the note is to discuss the translation of the numbers from one language to another in order to retain their meaning (in this case it is easy) and to preserve their connotations (and this is the hard part, as in every translation). The lexical system of numbers is an excellent laboratory to study the semiotic phenomena of hypocoding and hypercoding at an intermediate level of complexity, that does not avoid the problems but still allows rigorous solutions. This problem takes a well-defined role in the two sections dedicated to perception and connotations, when some numbers assume the role of hypernyms similar to adjectives "some, many, too many". The various languages do not use the same system of hypernyms, so the translation, beyond the literal meaning, requires a particular knowledge, typical of bilingualism.